EFFECT OF THE BANK OF RISK CAPITAL ADEQUACY RATIO (CAR) ON FOREIGN EXCHANGE NATIONAL PRIVATE BANKS - Debby Cynthia Ananda Sari; Herizon Herizon (STIE Perbanas Surabaya, 2016)
The purpose of the research is to determine LDR, IPR, NPL, APB, IRR, PDN, BOPO and FBIR simultaneously and partially have significant influence toward Capital Adequacy Ratio (CAR). Population were the On Foreign Exchange National Private Banks. Sampling technique is purposive sampling so that the selected Bank were PT. Bank ICBC Indonesia, Tbk, PT. Bank Permata, Tbk ,PT. Bank UOB Indonesia, Tbk , PT. Bank. Data collected by the methods of documentation and analysis were performed by linear multiple regression analysis technique.Results shows that LDR, IPR, NPL, APB, IRR, PDN BOPO, and FBIR simultaneously have significant effect toward CAR ratio On Foreign Exchange National Private Banks. Partially LDR ratio significantly has a positive effect on CAR ratio On Foreign Exchange National Private Banks and Partially BOPO ratio significantly has a negative effect on CAR ratio On Foreign Exchange National Private Banks. Meanwhile IPR , NPL, and PDN has a positive effect but insignificant toward CAR ratio On Foreign Exchange National Private Banks. On the other side, APB, IRR and FBIR have negative effect but insignificant toward CAR ratio On Foreign Exchange National Private Banks.